2, 4, 6‐Trichlorophenol degradation mechanism and microbial community analysis in an intimately coupled visible‐light photocatalysis and biodegradation system. Issue 9 (31st May 2022) - Liang, Yinna; Zhao, Tianyu; Xiao, Bing; Xiong, Jianhua; Wang, Shuangfei; Zhu, Hongxiang; Chen, Guoning; Song, Hainong; Huang, Shaobin
Abstract: BACKGROUND: Intimately coupled photocatalysis and biodegradation (ICPB) is a novel wastewater treatment technology with potential applications in the degradation of bio‐recalcitrant compounds. Although visible light has some advantages over UV light in the ICPB technology, it has never been used to treat 2, 4, 6‐trichlorophenol (2, 4, 6‐TCP)‐contaminated wastewater with this approach. RESULTS: TiO2 /sponge composites with good photocatalytic activity under visible light were prepared and used as biofilm supports to develop a novel ICPB system. The latter showed highly efficient degradation properties and could mineralize 2, 4, 6‐TCP, with performances superior to those of the individual biological and photocatalytic systems. The removal of 2, 4, 6‐TCP using the ICPB system reached almost 100% after 4 h, whereas the mineralization rate approached 83% after 12 h. The key feature of the presented ICPB method is that photocatalytic reactions can occur after detachment of biofilms from the outer surface of the composite, and the resulting photocatalytic products are biodegraded by the protected biofilms inside the composites. The interior of the composites exhibited a marked enrichment in Acinetobacter, Methylophilus, Pseudomonas, Acidovorax and Flavobacterium species, which played an important role in the ICPB system. CONCLUSIONS: This study introduces a new bio‐photocatalytic degradation system and provides insight into the mechanism of chlorophenol‐contaminated wastewater treatment using ICPB. © 2022 Society of Chemical Industry (SCI).